2011
DOI: 10.1039/c0cp01276a
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium nanoparticles embedded in mesoporous carbon microfibers: preparation, characterization and catalytic properties in the hydrogenation of d-glucose

Abstract: Ruthenium (Ru) nanoparticles dispersed in mesoporous carbon microfibers were prepared using alumina microfibers as the templates via a chemical vapour deposition (CVD) route. Characterized data showed that Ru nanoparticles were embedded in the mesoporous carbon matrix. The samples were found to possess a specific surface area as high as 750 m(2) g(-1), pore sizes in the range of 3-5 nm, lengths in the range of 5-10 μm, and a width of about 0.5 μm. The Ru catalysts displayed a remarkably high catalytic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 33 publications
(36 reference statements)
1
58
0
Order By: Relevance
“…Additionally, such peak overlaps with hcp and eventually fcc Ru planes (due to structural interactions with fcc Pt). Also, a low‐intensity reflection at 2 θ =69.5° in Figure a) can be attributed to the (110) Ru plane . Figure b) displays the deconvolution of the broad peak, showing the contributions of the (100), (002) and (101) hcp Ru reflections, as well as the (111) fcc Ru peak.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, such peak overlaps with hcp and eventually fcc Ru planes (due to structural interactions with fcc Pt). Also, a low‐intensity reflection at 2 θ =69.5° in Figure a) can be attributed to the (110) Ru plane . Figure b) displays the deconvolution of the broad peak, showing the contributions of the (100), (002) and (101) hcp Ru reflections, as well as the (111) fcc Ru peak.…”
Section: Resultsmentioning
confidence: 99%
“…Also, a low-intensity reflection at 2θ = 69.5°in Figure 3 a) can be attributed to the (110) Ru plane. [47] Figure 3 b) displays the deconvolution of the broad peak, showing the contributions of the (100), (002) and (101) hcp Ru reflections, as well as the (111) fcc Ru peak. These characteristics strongly suggest the formation of PtÀ Ru alloyed phases at Pt/rGO Ru-dim , with metallic Ru being formed from the organometallic compound.…”
Section: Physicochemical Characterization Of the Pt/rgo Pt/rgo Ru-dimentioning
confidence: 99%
“…Because of the superior mass transfer ability from micropore to liquid phase and the better desorption ability of sorbitol than the conventional carbon, woven rayon fabric derived active carbon cloths supported ruthenium showed outstanding performance in hydrogenation of glucose to sorbitol (99.5 selectivity at 99.7% conversion under the condition of 373 K, 8 MPa H2), according to research of Besson et al 105 Lin et al 106 Zhao et al 107 presented that Ru nanoparticles containing carbon microfibers showed higher activity in glucose hydrogenation than Ru supported on multi-walled carbon nanotubes, alumina microfibers and active carbon. The high activity and stability of this catalyst was attributed to the high degree of Ru dispersion, appropriate particle Ru size and high crystallinity.…”
Section: Hydrogenation and Hydrogenolysis Of Sugarsmentioning
confidence: 98%
“…[1,2,3,4,5,6,7,8] However, the production of nanostructured carbon supports often requires a number of preparation steps, such as template impregnation, pyrolysis and / or template removal procedures, including the usage of aggressive chemicals (e.g. Pd/Ru particles) has been of scientific interest since decades.…”
Section: Introductionmentioning
confidence: 99%